References to subjective and social aspects during isolation and social distancing in childhood and adolescence (Praxis Educativa, 2023)
The research covered several dimensions related to the transformations in daily and school life, produced by the measures of isolation and preventive and compulsory social distancing. In this paper, we will focus on those repercussions linked to the subjective from the perspective of adults when they talk about their children. In this sense, we share interpretations from a virtual survey carried out by 1280 families from different parts of the national territory, administered in the middle of 2021. At the same time, descriptive references to schooling in households are offered and relationships are articulated to work on the psychosocial effects that the emergency measures imposed, modifying family, school, social, and labour daily life. The qualitative analysis of the open-ended responses is made from a sociopsychogenetic perspective, allowing articulation of subjective, social, and cognitive aspects interpreted from a historical and relational perspective.
Keywords: family; school; psychosociology; pandemic; transformation